EVALUASI LINGKUNGAN AIR TANAH DI DAS CITARUM HULU - Indriatmoko, Robertus Haryoto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
The catchment area “Citarum” has been being in a very critical condition relating to extremely environmental problems. River water pollution in this catchment is obviously caused by industrial and domestic waste water. Nowadays the pollution load is already too high and the BOD, COD contents exceed the WHO standard. The activity evaluating groundwater environment in the up steam of the catchment area has the objective wich is to monitor the effect of groundwater pollution brought about by decreasing of surface water quality in upstream Citarum. The observed locations are village Suleman, Mekarrahayu, Margarahayu and Nanjung. They are all in Bandung regency. The four observed locations can be as representative for the three parts of upstream Citarum, ie. Upper, middle and lower part. Results of the evaluation are able to described groundwater quality condition, especially in the upstream Citarum cathment area.